Interlocking rhythmic composition style of Borneo ketebong - the Gendang Pampat - Sinin, Aaliyawani Ezzerin; Sinin, Hamdan; Mohamad Said, Khairul Anwar; M Duin, Ezra Alfandy (BioResources, 2024)
This work was conducted using the PicoScope signal extraction and Adobe Audition procedure, which revealed significant insights regarding the Iban traditional drum called ketebong. Three ketebong of different lengths, i.e., long, medium, and short sizes were studied. The amplitude of the long ketebong signal remains constant, showing that it had sustained its timbre for a longer duration compared to medium and short ketebong. Considering the diameter, all ketebong are almost similar, all the ketebong yield fundamental frequency at 50.15 Hz (i.e., G1# ~51.9 Hz). Although all ketebong showed similar fundamental frequency, Adobe Audition showed that the long ketebong has a brighter sound than the medium ketebong followed by the short ketebong. The purpose of this study is to derive the musical qualities of Gendang Pampat (GP), with a particular emphasis on the ketebong performance technique. The goal is to produce a rhythmic composition that integrates and reinforces a connected, expressive, rhythmic musical arrangement. The study aims to establish a framework by investigating the interlocking of rhythmic of GP to generate musical interpretation for composing a new repertoire for GP performance.